2010
DOI: 10.1111/j.1479-8425.2009.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Practitioners of vipassana meditation exhibit enhanced slow wave sleep and REM sleep states across different age groups

Abstract: Intense meditation practices influence brain functions in different ways and at different levels. Earlier studies have shown that meditation practices help to organize sleep-wake behavior. In the present study, we evaluated the sleep architecture of vipassana meditators across different age groups. Whole-night polysomnography was carried out in healthy male subjects between 30 and 60 years of age from control (n = 46) and meditation (n = 45) groups. They were further divided into younger-(30-39 years), middle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…A reduction in TST has been recently reported by another sleep study in LTM [45], and it indicates that meditation practice may decrease sleep needs. However other studies [46], [47] investigating sleep architecture didn't find a reduction of TST, suggesting that the sleep architecture is not the most reliable parameter to study the effect of meditation on neuronal plasticity during sleep. Consistent with this idea, we did not find a correlation between the changes in any traditional polysomnographic sleep parameters and meditation practice.…”
Section: Discussionmentioning
confidence: 88%
“…A reduction in TST has been recently reported by another sleep study in LTM [45], and it indicates that meditation practice may decrease sleep needs. However other studies [46], [47] investigating sleep architecture didn't find a reduction of TST, suggesting that the sleep architecture is not the most reliable parameter to study the effect of meditation on neuronal plasticity during sleep. Consistent with this idea, we did not find a correlation between the changes in any traditional polysomnographic sleep parameters and meditation practice.…”
Section: Discussionmentioning
confidence: 88%
“…Studies by Sulekha et al (2006) and Ravindra et al (2010) demonstrated the differences in sleep architecture in practitioners of Vipassana meditation (mindfulness meditation). The sleep architecture of senior practitioners of Vipassana meditation was endowed with enhanced states of SWS and REM sleep compared to that of non-meditating control group.…”
Section: Meditation Brain Functions and Sleepmentioning
confidence: 99%
“…Our finding is unexpected because practice of meditation has been associated with increased neuroplasticity [126][127][128], and is thought to have neuroprotective effects against cognitive decline [129] and psychopathology [130]. For instance, in one study [131] Vipassana practitioners showed no age-related decline in slow-wave sleep and REM sleep compared to controls, suggesting that Vipassana practice may protect against age-related neurodegeneration.…”
Section: Sleep Spindlesmentioning
confidence: 59%